The relationship between labour unions' bargaining power and firms' operating flexibility: New evidence from emerging markets - I. G. Choi; P. Sohn; J-Y. Seo (South African Journal of Business Management, 2015)
This study analyses the relevance between the bargaining power of labour unions and the operating flexibility on firms' capital costs by using non-financial firms listed on the Korean stock exchange from 1999 to 2013. Under the assumption that constraints in business activities attributed to the collective bargaining power of labour unions lead to reduced operating flexibility and increased capital costs, we test this notion empirically; the main test results are as follows: First, we find from portfolio analysis that the cost of capital is higher for firms in more unionized industries. Second, we find that union coverage positively affects the cost of capital at a significant level. Third, we confirm through robustness tests that the industry adjusted union coverage (IAUC) also has a positive effect on the cost of capital at a significant level. As a result, the effect holds after controlling for a host of industry- and firm-level characteristics, and is stronger when unions have more favourable bargaining power. Thus, our findings are consistent with the hypothesis that the increase of labour unions' bargaining power leads to raise firms' capital costs by decreasing operating flexibility in the Korean firms.
Keywords: 650